The Relationship of Leadership Styles and Organizational Culture Case Study of an Oil and Gas Company in Indonesia - Darwis, Tommy K; Djajadiningrat, Surna Tjahja (Jurnal Manajemen Teknologi, 2010)
This study explores relationship between leadership styles and organizational culture in an oil and Gas Company in Indonesia. The respondents are employees of an oil and Gas Company in Indonesia. This study  use  Multifactor  leadership  questionnaires  to  define  leadership  styles  and  Denison's Organizational Culture Model to measure Organizational Culture. These questionnaires were used to measure  leadership  styles  of  immediate  or  direct  supervisor  and  organizational  culture  of  unit  or division. The data were analyzed with descriptive and use correlational analysis.Arelationship exists between the leadership styles of immediate or direct supervisor and organizational culture. In three Leadership styles of Multifactor leadership, Positive correlation was found between Transformational Leadership Style and Organizational Culture. Transformational Leadership found as strong  predictor  of  organizational  culture. A positive  correlation  also  found  between Transactional Leadership  Style  and  Organizational  Culture  and  conversely,  Laissez-Faire  Leadership  style  has negative correlation with organizational culture. Transformational, Transactional Leadership and high level  of  organizational  culture  will  be make  good  impact  for maintaining  and  achieving  excellent organizational performance for company.Keywords:  Leadership  Styles,  Organizational  Culture, Transformational  Leadership,  Oil  and  gas Company in Indonesia